Basic Psychological Needs on Primary School Student Well-being - Deasyanti Deasyanti; Helmi Nurhasanah (Jurnal Pendidikan Humaniora, 2019)
Abstract: This study aimed  to test the effect of basic psychological needs toward the school well-being. This quantitative study uses a causal relationship research design. A total of 150 students were taken from six primary schools using a multi stage cluster random sampling technique. Data were  collected by using two types of instruments, namely instruments to measure basic psychological needs; and instruments to measure school well-being. Data then analyzed by using regression. The findings showed there was an effect of the basic psychological needs on school well being. The need for relatedness is the most predictor to school well-being; whereas the need of autonomy is not associated significantly with school well-being. Key Words: basic psychological needs, school well-being, self-determination theoryAbstrak: Penelitian ini bertujuan untuk menguji pengaruh kebutuhan dasar psikologis terhadap kesejahteraan sekolah. Penelitian kuantitatif ini menggunakan disain penelitian hubungan kausal. Sebanyak 150 siswa diambil dari enam Sekolah Dasar menggunakan Teknik multi stage cluster random sampling. Data dikumpulkan dengan menggunakan dua jenis instrumen, yakni instrumen untuk mengukur kebutuhan dasar psikologis; dan instrumen untuk mengukur kesejahteraan sekolah. Analisis data menggunakan regresi. Hasil penelitian membuktikan adanya pengaruh signifikan kebutuhan dasar psikologis terhadap kesejahteraan sekolah. Kebutuhan untuk keterkaitan merupakan prediktor yang paling besar terhadap kesejahteraan sekolah, sedangkan kebutuhan untuk mandiri tidak berpengaruh signifikan terhadap ke-sejahteraan sekolah.Kata kunci: kebutuhan dasar psikologis, kesejahteraan sekolah, teori determinasi diri